Antecedent factors of knowledge sharing in research - Khosravi, Arash (2013)
One of the most important goals of universities is the promotion of students as future professional knowledge workers. Therefore, knowledge-sharing and transferring at tertiary level between students and supervisors is vital in universities; this asset would help to decrease the budget and provide an affordable way of doing research. To achieve the aim of this study, (which was, namely: assessment of the impact of individual, organizational and technical factors on knowledge-sharing in a research supervision domain), a specific research model was developed. This model was based on systematically analyzing and extracting all the knowledge-sharing impact factors and then choosing adaptable ones, according to research supervision models. To effectively evaluate the research model, a quantitative research method was adopted. Data was collected by survey questionnaires from 150 students from the Faculty of Computing at Universiti Teknologi Malaysia. The Smart PLS tool was used for data analysis. In sum, the results of this research show that individual factor in a research supervision domain, namely: the ability of students to share knowledge, in addition to technological factors, specifically, IT systems have the greatest impact on knowledge-sharing in the supervision process. Also, organizational factors (culture of the university, social networks, and supervisor support) have a positive impact on knowledge-sharing in research supervision. However, when compared with individual and technical factors, the effect of an organizational factor on knowledge-sharing in research supervision is not particularly strong in the case of this study. There is not a positive relationship currently existing between learning strategy and knowledge-sharing in research supervision. Finally, this study is among the first of its kind to empirically examine the antecedent factors of knowledgesharing in the context of research supervision.